Analysis of Determining The Selling Price of Herbal Coffee Products at Sumber Kembang Farmer Group - Ardhiarisca, Oryza; Faizin, Nur; Putra, Rediyanto; Yuana, Dita Bitari Mei; Lestari, Datik (International Economic Conference of Business and Accounting, 2024)
The purpose of this study was to calculate the cost of goods produced and determine the selling price of herbal coffee products at Sumber Kembang Farmer Group. The product is a new product developed by the farmer group to improve the marketing of coffee products. This research is descriptive research, with the full costing method in determining the cost of production. Data were collected by interview and corroborated with documentation data. Furthermore, data analysis was carried out followed by drawing conclusions. The conclusion of this study is that the cost of production of herbal coffee per 100 gr package is IDR 18,982.18 and if a profit of 20% is assumed, the selling price of herbal coffee products is IDR 22,778.62 Furthermore, a comparison is made with the price of similar products on the market sold at IDR 30,000.00. Sumber Kembang Farmer Group Herbal Coffee products have the ability to compete with similar products on the market with a price difference of IDR 7,221.38.